Direct Chaotic Ultra-Wideband Wireless Communications in the Very High Frequency and Ultra High Frequency Radio Bands - Dmitriev, A. S.; Efremova, E. V.; Itskov, V. V.; Petrosyan, M. M.; Ryzhov, A. I.; Turkanov, I. F. (Journal of communications technology & electronics, 2022)
The problem of construction of ultra-wideband direct chaotic communication devices in the very high frequency and ultra high frequency ranges of radio waves is considered, the features of this range with respect to the propagation of electromagnetic radiation are discussed, and performance potential is evaluated. Experimental direct chaotic transceivers with a working band of 200–450 MHz, their structure, technical implementation, and characteristics are presented. The results of laboratory and field tests of prototypes are given to demonstrate transmission ranges of up to 1.5 km, which correspond to the calculated characteristics.